Dampak dari perilaku orang tua strict parents pada ‎perkembangan anak usia dini - Nurdin, Zilyanadelia Wahyu Veronellita (Maliki Interdisciplinary Journal, 2023)
The study aims to see how parents affect the development of children. As for the method in this study, it is to use a qualitative approach using literature studies. Where the discussions and theories are based on the analysis of several articles and journals. Where the result is that the protective behaviour of this parent or parental parents can have a negative influence on the development of the child. The study may indicate that an overprotective or parental attitude would make a child more likely to be a dependent child, a lack of social skills, a lack of emotional control, lack of confidence, and a lack of independence.